Notes on some Whaitsiids and Moschorhinids - Brink, A. S. (Bernard Price Institute for Palaeontological Research, 1959)
This paper contains descriptions of five genera. The first is a redescription of the type specimen of Notosollasia boonstrai, which has been additionally cleaned since it was first introduced. It has, lodged in its "throat", the crushed skull of a "Dicynodon" and circumstances indicate that the Notosollasia died while devouring its prey. The second specimen is recognised as perhaps representing the doubtful genus Notaelurops. It was earlier identified as a small Notosollasia longiceps. The third specimen is not a Whaitsiid, but being a contemporary form with some vague affinities to Moschorhinus, it is taken into consideration. It is named Hewittia albanensis gen. et sp. nov. A snout of Moschorhinus kitchingi, also mentioned in a previous publication, is redescribed and figured. The fifth specimen is a beautiful and complete skull of a new species, Moschorhinus natalensis, the first specimen of this genus that has the whole of the posterior half of the skull preserved and it is peculiar in that it dates from the Lystrosaurus-zone. An interesting new arrangement in the replacement of the canines in this family is analysed.
Main article
Keywords: Whaitsiid; Moschorhinid; Karoo